Guideline para identificação de sintomáticos respiratórios pela equipe de saúde da família - Brandão, Elma Galdino (2016)
Tuberculosis (TB) remains a major health problem throughout the world, requiring the development of strategies for their control, considering humanitarian, economic and public health. Brazil is the only Latin American country included among the twentytwo nations account for 80% of all TB cases in the world, occupying the 16th position in the number of new cases and the 22th position in relation to the incidence rate (CI), prevalence and mortality This study aimed to the construction by professional health team of the family of a guideline of care focused on identifying respiratory symptoms (SR), are opting as a methodological framework for the care Convergent Research. The survey was conducted with community health workers and nurses of Campina Grande Health Unit Health District VI. Data collection occurred in two stages: individual interviews and workshop, and analysis of these was used the case study. Through semi-structured interviews were established two categories "Strengths" and "Weaknesses" the operationalization of active search for respiratory second symptomatic attributes of APS that underpinned the discussions in the group workshop originated two axes of actions that supported the preparation of the guideline: "Qualification and expanding access to diagnosis and information "and" diagnostic Decentralization and organization flows ". As a final product all involved collectively built a service flowchart to respiratory symptoms. It is believed that these results, although reflecting a local reality can conceive thoughts on the team's role in TB control and effect on improving actions directed to the search and identification of SR, contributing to the early detection of disease and reduction complications and death associated with it, in view of presenting a new technology for care.